Pengaruh Pengembangan Soft Skills Terhadap Kesiapan Kerja: Kasus Lulusan Terbaru Dari Universitas Negeri - Aprilita, Kimtania Patricia; Pritasari, Adita (CV ODIS, 2024)
The Fourth Industrial Revolution has brought significant changes to the job market, causing a skills gap where many Indonesian graduates face unemployment due to a mismatch between their education and market needs. This study examines the influence of soft skills development on perceived work readiness among recent graduates from various public universities in Indonesia, focusing on five key soft skills: communication, problem-solving, time management, teamwork, and adaptability. The main issue addressed in this research is the lack of alignment between the skills developed during university education and those needed by employers, contributing to the high unemployment rate among graduates. A quantitative approach was used in this study, involving an online survey of 100 recent graduates who have secured full-time employment. The survey data was analysed using descriptive statistics and the Spearman-rho correlation test. The findings show a significant positive correlation between perceived work readiness and all examined soft skills. Communication, time management, and adaptability demonstrated a strong positive relationship, while problem-solving and teamwork showed an even stronger relationship. These results indicate that graduates with strong soft skills feel more prepared and capable of meeting job market demands. The study concludes that soft skills training is essential for improving graduates' work readiness. Universities should integrate more practical exercises and real-world problem-solving scenarios into the curriculum. Employers are also advised to offer specific training programs to help new employees transition into the workforce. Further research should explore the role of soft skills across various industries and education levels to understand how to prepare graduates for different job markets, including tracking the long-term impact of soft skills development in educational programs to bridge the gap between academic preparation and market needs, reduce unemployment, and enhance workforce readiness